Public support for local adaptation policy: The role of social-psychological factors, perceived climatic stimuli, and social structural characteristics. (January 2022) - Houser, Matthew; Gazley, Beth; Reynolds, Heather; Grennan Browning, Elizabeth; Sandweiss, Eric; Shanahan, James
Highlights: Little research has examined adaptation policy support at the subnational level. Developed a conceptual model for adaptation policy support. SEM analysis shows different factors shaped support of policy versus taxes. Response efficacy particularly impactful for both outcomes. Abstract: Climate change presents serious risks to human communities around the world. To ensure rapid, widespread and equitable adaptation to these risks, government policy must be enacted to support community-wide adaptation. Public support for adaptation policy will be key to its passage. To date, few studies have focused on what factors motivate public support for adaptation policy, especially at the subnational level. To address these gaps, we develop a conceptual model that draws on and synthesizes past conceptual frameworks and literature related to environmental behavior and adaptation specifically. Using structural equation modeling with latent variables, we examine this model, drawing on data from a statewide survey of over 2700 individuals from the state of Indiana in the Midwestern United States. We assess the drivers of two distinct measures of policy support: support for climate adaptation policy and support for climate adaptation taxes. We find that threat appraisal, climate risk perception, perceived efficacy of government, respondent's climate change beliefs, perceived descriptive and dynamic norms around policy support, and social structural characteristics such as political affiliation are important drivers of support for adaptation policy, but that their effects differ across our two outcome measures. These findings point to opportunities to better engage the public in policy discourse, while also suggesting that distinct motivations shape support for policy compared to the taxes likely needed to support these new programs.